2020
DOI: 10.3389/fnhum.2020.00340
|View full text |Cite
|
Sign up to set email alerts
|

Brain Processes While Struggling With Evidence Accumulation During Facial Emotion Recognition: An ERP Study

Abstract: The human brain is tuned to recognize emotional facial expressions in faces having a natural upright orientation. The relative contributions of featural, configural, and holistic processing to decision-making are as yet poorly understood. This study used a diffusion decision model (DDM) of decision-making to investigate the contribution of early face-sensitive processes to emotion recognition from physiognomic features (the eyes, nose, and mouth) by determining how experimental conditions tapping those process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 89 publications
(113 reference statements)
1
10
0
2
Order By: Relevance
“…We used face sketches as used in Yang et al (2020), which were generated from the Radboud Face Dataset (Langner et al, 2010). Number stimuli were generated at the beginning of the session for each participant, under the constraint that they were 3-digit integers.…”
Section: Classification Task With Different Sensory Modalitiesmentioning
confidence: 99%
“…We used face sketches as used in Yang et al (2020), which were generated from the Radboud Face Dataset (Langner et al, 2010). Number stimuli were generated at the beginning of the session for each participant, under the constraint that they were 3-digit integers.…”
Section: Classification Task With Different Sensory Modalitiesmentioning
confidence: 99%
“…Yang et al found that the N170 amplitude increases when there are modified face characteristics that make participants struggle with facial recognition. This indicates extra resource allocation for encoding a face when, for example, blocking certain areas of that face 17 . Liu et al found that Chinese opera masks elicited a reduced N170 amplitude as compared to normal faces 18 .…”
Section: Faces As Visual Stimulimentioning
confidence: 99%
“…Следующий за N170 высокоамплитудный компонент P200 имел в нашем исследовании пиковую латентность 210-220 мс и позитивные максимумы в задних отделах. Предполагается, что он отражает процессы различения стимулов и выбор ответа, отмечено влияние на него избирательного внимания и эмоциональности стимула в норме [16,17]. В нашем исследовании изменения в этом компоненте отражены в двух окнах -130-200 мс и 200-300 мс (см.…”
Section: результаты и обсуждениеunclassified